2014
DOI: 10.1111/sms.12281
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic profile of young swimmers: Changes over a competitive season

Abstract: The aim of this study was to analyze the changes in the hydrodynamic profile of young swimmers over a competitive season and to compare the variations according to a well-designed training periodization. Twenty-five swimmers (13 boys and 12 girls) were evaluated in (a) October (M1); (b) March (M2); and (c) June (M3). Inertial and anthropometrical measures included body mass, swimmer's added water mass, height, and trunk transverse surface area. Swimming efficiency was estimated by the speed fluctuation, stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 43 publications
(81 reference statements)
2
48
0
Order By: Relevance
“…Now, an intriguing question is which underlying performance characteristics (e.g., anthropometrical, technical, tactical, physiological, and psychological characteristics) contribute to the successful performance development toward top‐elite level. In here, it is important to consider that the underlying performance characteristics are influenced by maturation, learning, and training and that athletes always develop in and with their environment. The environment (e.g., parents, coaches, talent development programs, competition, and training facilities) plays a crucial role in developing the underlying performance characteristics .…”
Section: Discussionmentioning
confidence: 99%
“…Now, an intriguing question is which underlying performance characteristics (e.g., anthropometrical, technical, tactical, physiological, and psychological characteristics) contribute to the successful performance development toward top‐elite level. In here, it is important to consider that the underlying performance characteristics are influenced by maturation, learning, and training and that athletes always develop in and with their environment. The environment (e.g., parents, coaches, talent development programs, competition, and training facilities) plays a crucial role in developing the underlying performance characteristics .…”
Section: Discussionmentioning
confidence: 99%
“…The dv is a feasible way to analyze the swimmers' overall stroke mechanics, as it measures the ratio between the acceleration and deceleration within each stroke cycle, allowing to: identify critical points in the different phases of each cycle, and collect relevant data for practitioners and coaches. 15 Efficiency data collection…”
Section: Kinematic Data Collectionmentioning
confidence: 99%
“…A speedo-meter cord (Swim speedo-meter, Swimsportec, Hildesheim, Germany) was attached to the swimmer's hip (Barbosa et al, 2015). The speedo-meter was set on the forehead-wall of the swimming pool.…”
Section: Data Collectionmentioning
confidence: 99%
“…It was reported that ApEn was higher for elderly than young subjects in walking at 100 steps/ minute and 120 steps/minute (Arif, Ohtaki, Nagatomi & Inooka, 2004). In young swimmers, the ApEn decreased, becoming more predictble, over a season and this was coupled with a performance enhancement (Barbosa, Morais, Marques, Silva, Marinho & Kee, 2015). Thus, both land-based and aquatic locomotion seem to involve a given degree of unpredictability.…”
mentioning
confidence: 95%
See 1 more Smart Citation